2022
DOI: 10.3389/fimmu.2022.893512
|View full text |Cite
|
Sign up to set email alerts
|

Immune Mechanisms Underlying Hepatitis B Surface Antigen Seroclearance in Chronic Hepatitis B Patients With Viral Coinfection

Abstract: It is considered that chronic hepatitis B patients have obtained functional cure if they get hepatitis B surface antigen (HBsAg) seroclearance after treatment. Serum HBsAg is produced by cccDNA that is extremely difficult to clear and dslDNA that is integrated with host chromosome. High HBsAg serum level leads to failure of host immune system, which makes it unable to produce effective antiviral response required for HBsAg seroclerance. Therefore, it is very difficult to achieve functional cure, and fewer than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 170 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…Therefore, pursuing a better endpoint, HBsAg seroclearance, is important. HBsAg seroclearance, also called "functional cure", can effectively improve the long-term prognosis of patients and greatly reduce the risk of cirrhosis and liver cancer (18)(19)(20). Pegylated interferon a-2a (PEG-IFN a-2a) have a unique advantage over nucleoside (acid) analogues (NAs) in achieving HBsAg seroclearance (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pursuing a better endpoint, HBsAg seroclearance, is important. HBsAg seroclearance, also called "functional cure", can effectively improve the long-term prognosis of patients and greatly reduce the risk of cirrhosis and liver cancer (18)(19)(20). Pegylated interferon a-2a (PEG-IFN a-2a) have a unique advantage over nucleoside (acid) analogues (NAs) in achieving HBsAg seroclearance (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the expression of RANTES and MIP-1α in HBsAg negative group is higher than that in HBsAg positive group, which may contribute to the restoration and activation of immune function in HBsAg negative and HBV DNA positive patients. Existing studies have shown that HBsAg induces depletion phenotypes and dysfunction of T and B cells by leading to innate and adaptive immune deficiencies, so lowering serum HBsAg levels contributes to the recovery of host immune responses [57]. The decrease of HBsAg level can promote the reconstruction of host immune system: the antigen presentation ability of dendritic cells (DC) is restored, NK cell killing is restored, cytotoxic granules and IFN-γ secretion are increased, T cell activation is promoted, the proliferation ability of depleted T cells is restored, and the function of HBsAg specific plasma cells secreting anti-HBs is restored [58].…”
Section: Discussionmentioning
confidence: 99%
“…The HBeAg -positive status could be suggested as a surrogate marker for HBV viral load usually accompanied by high HBV DNA in patients with HIV/HBV coinfection ( Li et al., 2016 ), which ultimately results in immune activation and restoration. The HBeAg -positive stage generates less HBsAg than the HBeAg -negative stage because the chromosome integration level caused by HBV double -stranded linear DNA (dslDNA) becomes low ( Bill and Summers, 2004 ; Wu et al., 2022 ). Mutations in the precore region that occur over time in chronic untreated HBV infection lead to viral mutants that do not produce HBeAg and therefore HBeAg-negative disease, which is associated with periods of high viral replication and necro-inflammatory activity in the liver.…”
Section: Discussionmentioning
confidence: 99%